Food products in two cosmetic formulations: determination of the stability and toxicity - Martins, Vitor Manuel Ramalheira (2018)
The cosmetic market is extending to millions of consumers worldwide and its industry is worth tens of billions of US$. The competitive environment and the demands made by the consumers pushed the manufactures to develop new types of cosmetic products and to use new ingredients, such as bee products, to produce formulations with higher quality and efficacy.